Development and evaluations of the ancestry informative markers of the VISAGE Enhanced Tool for Appearance and Ancestry. (May 2023) - Ruiz-Ramírez, J.; de la Puente, M.; Xavier, C.; Ambroa-Conde, A.; Álvarez-Dios, J.; Freire-Aradas, A.; Mosquera-Miguel, A.; Ralf, A.; Amory, C.; Katsara, M.A.; Khellaf, T.; Nothnagel, M.; et al.
Abstract: The VISAGE Enhanced Tool for Appearance and Ancestry (ET) has been designed to combine markers for the prediction of bio-geographical ancestry plus a range of externally visible characteristics into a single massively parallel sequencing (MPS) assay. We describe the development of the ancestry panel markers used in ET, and the enhanced analyses they provide compared to previous MPS-based forensic ancestry assays. As well as established autosomal single nucleotide polymorphisms (SNPs) that differentiate sub-Saharan African, European, East Asian, South Asian, Native American, and Oceanian populations, ET includes autosomal SNPs able to efficiently differentiate populations from Middle East regions. The ability of the ET autosomal ancestry SNPs to distinguish Middle East populations from other continentally defined population groups is such that characteristic patterns for this region can be discerned in genetic cluster analysis using STRUCTURE. Joint cluster membership estimates showing individual co-ancestry that signals North African or East African origins were detected, or cluster patterns were seen that indicate origins from central and Eastern regions of the Middle East. In addition to an augmented panel of autosomal SNPs, ET includes panels of 85 Y-SNPs, 16 X-SNPs and 21 autosomal Microhaplotypes. The Y- and X-SNPs provide a distinct method for obtaining extra detail about co-ancestry patterns identified in males with admixed backgrounds. This study used the 1000 Genomes admixed African and admixed American sample sets to fully explore these enhancements to the analysis of individual co-ancestry. Samples from urban and rural Brazil with contrasting distributions of African, European, and Native American co-ancestry were also studied to gauge the efficiency of combining Y- and X-SNP data for this purpose. The small panel of Microhaplotypes incorporated in ET were selected because they showed the highest levels of haplotype diversity amongst the seven population groups we sought to differentiate. Microhaplotype data was not formally combined with single-site SNP genotypes to analyse ancestry. However, the haplotype sequence reads obtained with ET from these loci creates an effective system for de-convoluting two-contributor mixed DNA. We made simple mixture experiments to demonstrate that when the contributors have different ancestries and the mixture ratios are imbalanced (i.e., not 1:1 mixtures) the ET Microhaplotype panel is an informative system to infer ancestry when this differs between the contributors. Highlights: 226 ancestry (BGA) markers compiled for VISAGE Enhanced Tool (ET) combined with 184 appearance markers in one MPS assay. Autosomal BGA SNP number in ET reduced to allow inclusion of 85 Y-SNPs, 16 X-SNPs and 21 Microhaplotypes (MHs). Extra BGA markers give enhanced detail of co-ancestry patterns in admixed males and MH loci allow ancestry-based mixed DNA. Comprehensive reference population datasets and analyses of global distribution of variation in the ET BGA markers outlined. Expanded Middle East-informative SNPs enhance differentiation of these populations particularly when combined with nested K:5 STRUCTURE runs.